Análise do comportamento dos pilares mistos considerando a utilização de conectores de cisalhamento - Bianchi, Flavia Regina (2002)
The steel-concrete composite structures are systems that involve the interaction of structural steel components with concrete elements to resist external forces. This interaction between steel and concrete should be guaranteed to ensure that loads are supported. As such, adhesion tensions between the concrete and the steel should not be exceeded. In cases where they are, the use of shearing connectors becomes necessary. The influence of the use of shearing connectors in composite columns is greatly undervalued in the majority of scientific papers, with its use recommended only in situations of high vibration. In this paper, the behavior of composite columns is analyzed with the use of shearing connectors taken into consideration through numerical analysis using Ansys programming and based on the finite element method. To achieve this, an ideal model that reflects the situation was adopted permitting as study of the element, the load, and the contour conditions adequate for usage. Composite columns with and without shearing connectors were modeled. A load was applied to each model with varying eccentricity to create an interaction curve defining the moment of flexion in function of normal force. From the interactive curves that were constructed, the importance of the use of shearing connectors was analyzed. This analysis compares results to data supplied by EUROCODE 4(1994) and the influence of different values for maximum adhesion tension of the last load of the composite column.